Assessment of damage caused by mining fly Chromatomyia aprilina Goureau, 1851 larvae to leaf surface of fly honeysuckle (Lonicera xylosteum L.) in the conditions of Central Botanical Gardens of the National Academy of Sciences of Belarus - Volosach, Marina V. (Journal of the Belarusian State University. Ecology, 2020)
Based on the data, obtained by processing the herbarium collections of fly honeysuckle leaves (Lonicera xylosteum L.) damaged by mining fly (Chromatomyia aprilina Goureau, 1851) larvae carried out in the green areas of the Central Botanical Garden of the National Academy of Sciences of Belarus (Minsk) in October 2018, that included scanning and subsequent processing of obtained images by computer planimetry methods, it was found that the area of individual mines of Ch. aprilina on L. xylosteum leaf blades by the end of the growing season ranged from 0.04 cm 2 to 4.97 cm 2 , the total area – 0.17–4.97 cm2. The relative area of the damaged leaf surface varied from 1.13 to 52.92 %. A correlation between the area of individual mines and the total area of leaf blades where they have been formed was not revealed. It was shown that the area of individual mines cannot be used as a criterion for determination of Ch. aprilina larval instars.
Keywords: leaf mines; green areas; phyllobionts; Diptera; Agromyzidae